1996
DOI: 10.1021/ja953220z
|View full text |Cite
|
Sign up to set email alerts
|

Bromonium Ion Addition to Triruthenium and Triosmium Dodecacarbonyl:  The Markedly Different Structures of the [M3(CO)12(Br)]+ (M = Ru, Os) Ions

Abstract: Recently, Brown and co-workers reported the use of the bromonium ion of adamantylideneadamantane, as the triflate salt ([AdAdBr](OTf)), to transfer Br + to acceptor olefins. 1 On the other hand, work from this laboratory has shown that reaction of iodine with Os 3 (CO) 12 proceeds via the [Os 3 (CO) 12 -(I)] + cation, and it was suggested that bromination of Os 3 (CO) 12 proceeded through a similar intermediate. 2 Here we report the use of the bromonium ion reagent to prepare the [M 3 (CO) 12 -(Br)] + (M ) Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The X-ray crystal structure of the cluster cation in 2a (Figure ) shows that the osmium−osmium edge carrying the two group 15 substituents has been cleaved (Os(1)···Os(2) distances of 4.038(5) and 4.027(7) Å for 2a and 2b , respectively) to form an open bromonium-bridged compound. Their structures are similar to that of the earlier reported [Os 3 (CO) 12 (μ-Br)] + , and they may thus be viewed as group 15 substituted derivatives of the latter cluster cation …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The X-ray crystal structure of the cluster cation in 2a (Figure ) shows that the osmium−osmium edge carrying the two group 15 substituents has been cleaved (Os(1)···Os(2) distances of 4.038(5) and 4.027(7) Å for 2a and 2b , respectively) to form an open bromonium-bridged compound. Their structures are similar to that of the earlier reported [Os 3 (CO) 12 (μ-Br)] + , and they may thus be viewed as group 15 substituted derivatives of the latter cluster cation …”
Section: Resultssupporting
confidence: 85%
“…Essentially, the two major possibilities are via a radical mechanism or a bromonium intermediate . It has recently been shown that the reaction of Br + with the parent carbonyl cluster Os 3 (CO) 12 gave the bromonium cluster [Os 3 (CO) 12 (μ-Br)] + , and it was also demonstrated that this cluster was not the intermediate involved in the direct bromination reaction . In contrast, we have recently reported that the bromination of the substituted clusters Os 3 (CO) 11 (EPh 3 ) (E = P, Sb) gave two isomeric products, (Br) 2 Os(CO) 3 Os(CO) 4 Os(CO) 4 (EPh 3 ) and (Br)(OC) 4 OsOs(CO) 4 Os(CO) 3 (Br)(EPh 3 ) and suggested that the intermediate was a bromonium cluster with a terminal Br atom …”
Section: Introductionmentioning
confidence: 99%
“…Instead, Brown prepared the triflate salt 2-OTf,b ut also the triflate interacts with the bromiranium ion. [17] For its preparation we used as alt metathesis reactionw ith sodium tetrakis[3,5-bis(trifluoromethyl)-phenyl]b orate (NaBArF).T he stoichiometric addition of NaBArF to 2-Br 3 in dichloromethanea tr oom temperature formed 2-BArF (Scheme 2). Furthermore,t he triflate is still nucleophilic and 2-OTf reacts with cyclohexenet og ive 2bromocyclohexyl triflate.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a bromiranium salt with a weakly‐coordinating anion we chose to prepare the salt 2‐BArF . This salt has been used previously as a halogenating agent for an osmium carbonyl complex, but no procedure for its preparation or data on its reactivity have been reported . For its preparation we used a salt metathesis reaction with sodium tetrakis[3,5‐bis(trifluoromethyl)‐phenyl] borate (NaBArF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation